2015
DOI: 10.1021/acscatal.5b00357
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carbon-Resistant Dry Reforming Fe-Ni Catalyst: Role of Fe

Abstract: A series of bimetallic Fe-Ni/MgAl2O4 catalysts with Fe/Ni ratios between 0 and 1.5 have been examined for methane dry reforming at 923–1073 K, atmospheric pressure, and a CH4/CO2 ratio of 1. The evolution of the catalyst structure during H2 temperature-programmed reduction (TPR), CO2 temperature-programmed oxidation (TPO), and dry reforming is examined using time-resolved in situ X-ray diffraction (XRD). During H2-TPR up to 973 K, Fe2O3 and NiO are reduced to Fe and Ni. Higher temperatures lead to Fe-Ni alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
312
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 424 publications
(342 citation statements)
references
References 65 publications
27
312
2
1
Order By: Relevance
“…1) gone, while diffractions now appeared at angles lower than metallic Ni. This shift was attributed to formation of a Fe-Ni alloy (44 and 51.5 ), which was also observed in previous reports [41,43]. The intense diffraction peak at 45 could in part originate from residual metallic Fe, which was not engaged in alloy formation.…”
Section: Materials Characterizationsupporting
confidence: 84%
See 1 more Smart Citation
“…1) gone, while diffractions now appeared at angles lower than metallic Ni. This shift was attributed to formation of a Fe-Ni alloy (44 and 51.5 ), which was also observed in previous reports [41,43]. The intense diffraction peak at 45 could in part originate from residual metallic Fe, which was not engaged in alloy formation.…”
Section: Materials Characterizationsupporting
confidence: 84%
“…By fitting a Gaussian function to a diffraction peak, the crystallite size was determined from the peak width via the Scherrer equation, while the peak position gave information about the lattice spacing based on the Bragg law of diffraction: 2dsin(u) = nl [40]. A more detailed characterization of the Ni-Fe/MgAl 2 O 4 can be found in a previous work [41].…”
Section: Characterizationmentioning
confidence: 99%
“…For Ni-Fe materials, it was found that the catalytic activity in the dry reforming of methane increased as compared with monometallic Ni, since a larger Ni dispersion could be achieved [22]. Besides, because of the electronic effect created via metal-metal interactions, the formation of nickel carbide (coke precursor) could be largely avoided, thus leading to less deactivation occurring [23].…”
Section: Introductionmentioning
confidence: 99%
“…In theory, coke deposition can be avoided by: (i) altering the electronic properties of metal-support interactions, (ii) influencing the size of metallic particles and, (iii) improving the oxygen storage capacity and mobility within supporting material (Roh et al, 2006;Kumar et al, 2007;Chen et al, 2008;Goula et al, 2014;Yentekakis et al, 2015Yentekakis et al, , 2016Han et al, 2017). Thus, the attempts that have been undertaken to improve the stability of DRM nickel catalysts have focused on the use of different oxides as supports (e.g., Al 2 O 3 , SiO 2 , La 2 O 3 , CeO 2 , ZrO 2 ) (Pompeo et al, 2007;Bereketidou and Goula, 2012;Li et al, 2016) or the use of a variety of dopants that include transition metals (e.g., Fe, Co, Sn) (Ay and Uner, 2015;Theofanidis et al, 2015;Zhao et al, 2016), noble metals (e.g., Ag, Pt, Pd, Ir) Yentekakis et al, 2015;Yu et al, 2015), lanthanide metals (e.g., La, Ce, Pr) (Goula et al, 2016a;Vasiliades et al, 2016;Xiang et al, 2016) and alkaline earth metals (e.g., Sr, Ca, Ba) (Bellido et al, 2009;Sutthiumporn and Kawi, 2011). Although ZrO 2 is an oxide with a relatively low surface area, its notable thermal stability, strength and toughness, as well as, the fact that it is an acid-basic bi-functional oxide (as it contains both basic and acidic properties over its surface that have the capacity to work either independently or in cooperation), which has redox functions, makes it attractive for use in reforming reactions (Sarkar et al, 2007;Goula et al, 2017;Charisiou et al, in press).…”
Section: Introductionmentioning
confidence: 99%